Stage I‐laparoscopy partial ALPPS procedure for perihilar cholangiocarcinoma. Issue 6 (18th February 2020) - Balci, Deniz; Kirimker, Elvan Onur; Üstüner, Evren; Yilmaz, Ali Abbas; Azap, Alpay
Abstract: The treatment for perihilar cholangiocarcinoma (PHC) is a challenge for the surgeon requiring complex resections with a reported perioperative mortality rate between 15% and 48%. In PHC patients with future liver remnant (FLR) less than 30%, it is advised that hepatectomy can be safely performed after the FLR is modified. Associating Liver Partition and Portal vein ligation for Staged Hepatectomy (ALPPS) procedure is criticized heavily due to its high morbidity and mortality rate in this setting. Hereby, we are reporting a modification of ALPPS procedure for PHC. Clinical presentation, preoperative work‐up as well as operation and postoperative course of two cases were described in detail. Both patients were jaundiced preoperatively, stage 1 partial‐ALPPS procedures were performed laparoscopically, there was sufficient remnant hypertrophy during the interval stage and there was no posthepatectomy liver failure after the second stage (Supporting Information Video). We have followed patients with a mean follow up of 35 months without any recurrence. Here we describe the key technical aspects of this approach that are discussed in three parts: minimally invasive first stage, biliary drainage of both FLR, and deportalized liver at first stage and biliary reconstruction at the second stage. This technique, in selected patients, can extend the indication of ALPPS procedure for PHC with preoperative jaundice.